2015
DOI: 10.1155/2015/173970
|View full text |Cite
|
Sign up to set email alerts
|

Serum Caveolin-1 as a Novel Biomarker in Idiopathic Pulmonary Artery Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a rare disease but with significant morbidity and high mortality. There is no specific way to diagnose PAH. Thus, an easy used with good sensitivity and specificity biomarker of PAH is highly desirable to aid in the screening, diagnosis, and follow-up. Caveolin-1 (Cav1) is the structural protein of caveolae and is highly expressed in type I pneumocytes. Lungs tissues from idiopathic PAH (IPAH) patients showed decreased expression of Cav1 in vascular endothelial cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…[22][23][24] In addition, human studies support the role of CAV1 in PAH, with reduced caveolin-1 expression found to occur in the lungs of PAH patients regardless of mutation, and reduced systemic caveolin-1 levels. [25][26][27] A recent study found a CAV1 mutation in a child also with lipodystrophy, connecting these two metabolic disorders. 28 However, the manner by which CAV1 mutations promote PAH pathogenesis in humans remains incompletely elucidated.…”
Section: Additional Genes Believed To Cause Pah When Pathogenic Mutatmentioning
confidence: 98%
“…[22][23][24] In addition, human studies support the role of CAV1 in PAH, with reduced caveolin-1 expression found to occur in the lungs of PAH patients regardless of mutation, and reduced systemic caveolin-1 levels. [25][26][27] A recent study found a CAV1 mutation in a child also with lipodystrophy, connecting these two metabolic disorders. 28 However, the manner by which CAV1 mutations promote PAH pathogenesis in humans remains incompletely elucidated.…”
Section: Additional Genes Believed To Cause Pah When Pathogenic Mutatmentioning
confidence: 98%
“…33 Genetic deletion of caveolin-1 abrogates endotheliumderived hyperpolarizing factor (EDHF)-induced hyperpolarization by altering calcium entry, thus highlighting the role of caveolin-1 in EDHF regulation. 34 Caveolin-1 inhibits a number of proliferative pathways. Downregulation of caveolin-1 leads to hyperactivation of mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) pathway.…”
Section: Caveolin-1mentioning
confidence: 99%
“…However, its secretion in vascular endothelial cells is decreased in patients with PH, and a serum cutoff of 17.17 pg/mL is highly suggestive of idiopathic PH. 14 …”
Section: Use Of Biomarkers In Phmentioning
confidence: 99%
“…However, its secretion in vascular endothelial cells is decreased in patients with PH, and a serum cutoff of 17.17 pg/mL is highly sugges tive of idiopathic PH. 14 Elastin is a structural constituent of blood vessels, and its synthesis requires crosslinking of monomers by two amino acids, desmosine and isodesmosine. In patients with PH, elas tin turnover is elevated, and consequently, plasma and urine levels of desmosine and isodesmosine are high.…”
Section: Use Of Biomarkers In Phmentioning
confidence: 99%